Development of metabolic phenotype in phenylketonuria: evaluation of the blaskovics protein loading test at 5 Years of age - Burgard, Peter; Mönch, Eberhard; Zschocke, Johannes; Wendel, U.; Langenbeck, Ulrich (JIMD reports, 2016)
Background: As part of the German Collaborative Study on Phenylketonuria (PKU)/Hyperphenylalaninaemia (HPA) Study Protocol, a Blaskovics protein loading test (180 mg phenylalanine (phe) protein equivalent per kg body weight and day for 72 h) had been applied to 145 children at the age of 6 months. For investigating possible age-related changes of metabolic phenotype, 51 of them received a 2nd loading test at 5 years of age. Methods: Besides the analysis of blood phe levels, acidic phe transamination metabolites were quantified in urine. Results: Compared to the 6-month data, the mean blood phe level 72 h after start of loading (Phe72) was found to be decreased by 7% (P = 0.06), whereas the mean urinary excretion (per 1.73 m2 body surface and day) of 2-hydroxyphenylacetic acid was increased 1.9-fold (P < 0.01). Corresponding with these analytical data, the kinetic model constant k out of metabolic plus renal phe disposal was found increased 1.3-fold in mean (P < 0.01).In 3 of the 51 patients, Phe72 was very high at 6 months while in the medium range at 5 years, suggesting that catabolic states may mimic a more severe metabolic defect.The blood phe level response of mild PKU (type II) was assigned identically at both ages in 7/9 patients. Diverging results were (i) response type III (mild hyperphenylalaninaemia) at 6 months and type II at 5 years and (ii) type II at 6 months and type III at age 5. Conclusion: Renal elimination of OHPAA and phe tolerance increase significantly between the age of 6 months and 5 years, suggesting that, at least in childhood, formation and/or renal disposal of phe transamination metabolites may be major distal determinants of phe tolerance.
First Online: 19 December 2015
Gesehen am 25.05.2020